KNOWLEDGE AND PRACTICE PREVENTION OF ANEMIA IN WOMEN OF REPRODUCTIVE AGE IN BINH DUONG HOSPITAL IN 2019 (Vietnam Journal of Community Medicine, 2022)
Objectives: Determine the rate of knowledge and practice about anemia prevention in women of reproductive age to come to the hospital in Binh Duong province in 2019.Methods: Descriptive cross-sectional study. The study was conducted by direct interviewing the research subjects according to the structure questionnaire.Results: Anemia knowledge score of research subjects is very low, average 26.2 ± 3.9 points (scale of 0-51). The practical score of anemia prevention subjects of the research subjects averaged 7.7 ± 1.8 points (scale of 0-11). The percentage of common knowledge about anemia prevention among women of childbearing age is very low, only 12.4%, but the rate of good general practice is relatively higher at 52.2%. The rate of good practice in the group of 40-49 years old was lower than that of the group of 18-29 years old (OR=0.32; 95%CI: 0.12-0.78; p
Keywords: Knowledge, practice, nutritional anemia, women of childbearing age.